Early Dual-Antiplatelet Therapy at the Emergency Department Is Associated with Lower In-Hospital Major Adverse Cardiac Event Risk among Patients with Non-ST-Elevation Myocardial Infarction. (22nd April 2021) - Yang, Jen-Han; Shih, Hong-Mo; Pan, Yan-Cheng; Chang, Shih-Sheng; Li, Chi-Yuan; Yu, Shao-Hua
Abstract : Background . Dual antiplatelet therapy (DAPT) is a standard treatment in non-ST-segment-elevation myocardial infarction (NSTEMI). However, the timing of initiation of DAPT in the Emergency Department (ED) is not well established. The purpose of this study is to demonstrate the correlation between the different timings of DAPT initiation in ED and the outcomes in patients with NSTEMI. Method . We retrospectively collected data of patients who were diagnosed as NSTEMI in the ED of China Medical University Hospital during 2016 to 2019. All NSTEMI patients who required coronary stenting or ballooning were enrolled into the study, which means NSTEMI patients who received percutaneous coronary intervention (PCI) were included. The time interval between ED arrival and DAPT given was recorded. Patients were divided into 2 groups according to whether they received DAPT within 6 hours after arrival to the ED. The primary outcomes were in-hospital major adverse cardiovascular events (MACE). The secondary outcomes were unexpected return to the ED within 72 hours, readmission within 14 days, and revascularization procedures performed within the first 30 days. Results . 938 NSTEMI patients with PCI were enrolled. Patients who received DAPT beyond 6 hours were relatively old (65.70 ± 14.13 versus 63.16 ± 13.31, p = 0.014 ) and had relatively more comorbidities and higher Killip scores than those who received DAPT within 6 hours. The group that received DAPT within 6 hours had lower in-hospital MACE rate (3.52% versus 8.37%, p = 0.009 ). Multivariate logistic regression showed the group beyond 6 hours was independently associated with higher risk for in-hospital MACE rate (OR : 2.09, 95% CI 1.07–4.07, p = 0.030 ). Conclusion . Among patients with NSTEMI, DAPT beyond 6 hours after ED arrival have higher in-hospital MACE rate than those within 6 hours.